2014
DOI: 10.1007/s00011-014-0746-0
|View full text |Cite
|
Sign up to set email alerts
|

Water-soluble phenol TS-13 combats acute but not chronic inflammation

Abstract: The data suggest that the anti-inflammatory effects of Keap1/Nrf2/ARE system are more prominent against acute innate-mediated inflammation than chronic immune inflammation. This narrows the potential therapeutic efficacy of ARE inducers in inflammation treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 33 publications
0
4
0
4
Order By: Relevance
“…tBHQ inhibits IL-2 and CD25 expression, which correlates with decreased NFκB transcriptional activity in the cell [56]. As for treatment with TS-13, also has an anti-inflammation activity [33], we shown downregulation of p50 and p65 subunits of NFkB [34]. …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…tBHQ inhibits IL-2 and CD25 expression, which correlates with decreased NFκB transcriptional activity in the cell [56]. As for treatment with TS-13, also has an anti-inflammation activity [33], we shown downregulation of p50 and p65 subunits of NFkB [34]. …”
Section: Discussionmentioning
confidence: 95%
“…In particular, some phenolic antioxidants, namely, classic phase II inducers, have an anti-inflammatory effect [9, 27, 28], which is thought to be mediated by activation of Nrf2 [29, 30], inhibition of nuclear factor κB (NFkB; a key regulator of immune and inflammatory responses) [27, 30, 31], and by influence on MAPKs engaged in complex crosstalk between Nrf2 and NFkB pathways [32]. The anti-inflammatory effect of TS-13 was shown on in vivo models of acute inflammation [33]. We have recently shown that the mechanism of this effect may be related to downregulation of p65 and p50 subunits of NFkB and reduced phosphorilation of activating transcription factor 2 (ATF-2) [34].…”
Section: Introductionmentioning
confidence: 99%
“…рис. 5) на клетках линии J774 и ранее на клетках аденокарциномы молочной железы человека MCF-7 [20]), in vivo увеличивать экспрессию мРНК, содержание белка и активность GSTP1, а также образование комплексов ядерных белков с олигонуклеотидной последовательностью, соответствующей ARE (гель-ретардационный анализ) [21]).…”
Section: результаты и их обсуждениеunclassified
“…Существует общее мнение, что Nrf2 оказывает протективный эффект в отношении системных инфекций за счет влияния на NF-κB и модулирования экспрессии провоспалительных генов в макрофагах [16]. Ранее показано, что оригинальный синтетический монофенол ТС-13, индуцирующий Nrf2зависимый сигнальный путь в экспериментах in vitro [3] и in vivo [8] и ингибирующий NF-κBопосредованный сигналинг in vivo [14], обладает выраженным защитным эффектом in vivo в отношении острых воспалительных процессов, увеличивая выживаемость животных при септическом шоке [8].…”
Section: рис 1 динамика выживаемости мышей после инфицирования M Tunclassified
“…На 30 сутки после инфицирования в печени животных, получавших с питьевой водой антиоксидант ТС-13, наблюдалось достоверное снижение численной плотности гранулем (в 2,5 раза) и их диаметра (на 30 %). В экспериментах на мышах и крысах показано, что ТС-13 обладает выраженным защитным эффектом in vivo в отношении острых воспалительных процессов, способствуя уменьшению продукции АКМ и выраженности окислительного стресса, увеличивая выживаемость животных (септический шок) [8].…”
unclassified